First enantiospecific synthesis of (+)-beta-herbertenol - Chavan, Subhash P.; Thakkar, M.; Kharul, Rajendra K.; Pathak, A. B.; Bhosekar, Gaurav V.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
The first enantiospecific synthesis of (+)-beta-herbertenol, from naturally occurring R-(+)-citronellal, employing Taber's diazo decomposition protocol as the key step, is described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: citronellal; diazo decomposition; enantiospecific